Kedudukan Ahli Waris Pengganti (Patah Titi) menurut Hukum Adat Aceh dan Kompilasi Hukum Islam Pada Masyarakat Aceh: Studi Lapangan, Gampong Kuta Lhoksukon, Kabupaten Aceh Utara - Lia Safriana; hasim purba; Rosnidar Sembiring (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The position of substitute heirs (patah titi) in Acehnese society reveals a tension between customary law and the Compilation of Islamic Law (KHI). Acehnese customary law recognizes the concept of patah titi, which eliminates the inheritance rights of grandchildren when their parent dies before the testator, whereas Article 185 of the KHI recognizes and protects such rights. A field study conducted in Gampong Kuta, Lhoksukon, North Aceh Regency found that a portion of the community still upholds this customary concept. Harmonization between customary values and Islamic law is key to achieving justice and legal certainty for substitute heirs in Aceh.